2010
DOI: 10.1037/a0021046
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of emotional labour on emotional exhaustion and dedication of teachers.

Abstract: A great number of teachers find teaching fulfilling and are dedicated to it, but others feel emotionally exhausted, indicating that the interaction with pupils can be emotionally demanding. Emotional labor was shown to play an important role for the health of teachers. In a full two-wave longitudinal study over the period of 1 year, the effect of emotional labor on emotional exhaustion and dedication of 102 teachers was investigated. Teachers who were able to influence their emotions to feel the emotion approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 53 publications
12
111
2
6
Order By: Relevance
“…In practice, it may mean showing enthusiasm while conducting classes, reacting with empathy to pupils' worries and needs, hiding fatigue and annoyance or displaying positive emotions even when pupils are being difficult and rude. Teachers have to educate and, at the same time, manage their own emotions to meet the expectations associated with their profession [1,2]. In other words, they perform emotional labor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, it may mean showing enthusiasm while conducting classes, reacting with empathy to pupils' worries and needs, hiding fatigue and annoyance or displaying positive emotions even when pupils are being difficult and rude. Teachers have to educate and, at the same time, manage their own emotions to meet the expectations associated with their profession [1,2]. In other words, they perform emotional labor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that strained relationships with students and their parents as well as with supervisors and colleagues may be one of performed on a daily basis by nurses, police officers, retail sales, bank and hotel employees [4][5][6][7][8]. Recent research has also focused on teachers as "emotional laborers" [2,[9][10][11]. It has been stressed that emotional involvement is an integral part of the teaching profession [1,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on the COR model, positive results can follow when employees are able to meet demands (Philipp & Schüpbach, 2010). Employees' emotional labor strategies are selected with a view toward minimizing resource use and maximizing their personal gains (Mahoney et al, 2011).…”
Section: Main Effects Of Surface Acting On Job Satisfaction and Job Pmentioning
confidence: 99%
“…The suppression of negative emotions may create further negative emotions for teachers, such as guilt, regret, and shame, because they may think that it is inappropriate or even immoral for them as teachers to dislike or hate students (Hebson, Earnshaw, & Marchington, 2007;O'Connor, 2008). In addition, teachers may also feel emotionally uncomfortable or self-estranged, because their displayed emotions do not correspond to their true feelings (Hu¨lsheger et al, 2010;Philipp & Schu¨pbach, 2010). Both conditions may affect their professional identity and self-esteem, which in turn creates other intense negative emotions like frustration and depression (Hargreaves, 1998a;O'Connor, 2008).…”
Section: Journal Of Sociological Researchmentioning
confidence: 99%